Export Diversification of the Arkhangelsk Oblast’s Forestry Complex - Igor G. Muraev; Olga P. Sushko (Арктика и Север)
The decrease in the volume of exports of forest products from the Arkhangelsk Oblast is a significant problem for the region’s economy. This study aims to conduct a comprehensive analysis of the current situation and identify the prospects for development of forest products exports in the region. The export volume of forest products from the Arkhangelsk Oblast in 2023 significantly decreased compared to 2021. In the conditions of sanctions pressure, Russian forestry enterprises have to look for alternative markets. Despite the steps being taken to diversify exports, companies face difficulties in establishing business ties with foreign partners due to fears of secondary sanctions. This leads to a reduction in supply volumes and, as a result, a decrease in income from export activities. In addition, the domestic market is experiencing a negative impact due to a decrease in exports. Reduced external demand for wood creates an oversupply in the domestic market, which leads to a drop in prices. Such changes have a destructive impact on the financial well-being of enterprises in the Arkhangelsk Oblast, the economy of which depends on the forestry sector. In 2021, the Arkhangelsk Oblast exported timber to Asia, Europe, Africa, North and South America and even to the countries of Oceania. After the sanctions restrictions, the country structure of timber exports has changed dramatically. China became the main importer of timber from the Arkhangelsk Oblast. In the course of the study, the key directions of export diversification were identified and effective measures for their implementation were developed. Diversification of production and development of new markets will allow the Arkhangelsk forestry complex to overcome the negative consequences of export specialization and keep the leading positions in the Russian forestry sector.